Understanding the role of the actin cytoskeleton in vesicle trafficking to restrict growth of Drosophila epithelia - Gaspar, Pedro Miguel Coruche (2010)
Tese de mestrado, Biologia (Biologia Evolutiva e do Desenvolvimento), 2008, Universidade de Lisboa, Faculdade de Ciências